2014
DOI: 10.1002/2013jd021260
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of different atmospheric ozone retrievals and its effect on temporal trends and radiative transfer simulations in the Iberian Peninsula

Abstract: Uncertainty in total ozone column (TOC) values is quantified for eight different databases through a direct comparison with ground-based data at three Spanish locations, the maximum uncertainty being about 10.5 Dobson unit. A long-term TOC series is constructed using the mentioned databases from 1950 to 2011 for nine locations in the Iberian Peninsula. The monthly TOC climatology in the nine locations is presented. An exhaustive analysis is performed of TOC series trends and their statistical significance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…TOC evolution in the Iberian Peninsula was studied in depth by Román et al (2014d) in the dimming and brightening periods, with usually negative but not statistically significant trends being reported in both periods, and a statistically significant trend of −0.7 % dc −1 (percent per decade units) in the annual TOC between 1950 and 2011. Antón and Mateos (2013) showed that these TOC changes have no significant influence on SW radiation (e.g.…”
Section: R Román Et Al: Erythemal Ultraviolet Irradiation Trends Inmentioning
confidence: 99%
See 4 more Smart Citations
“…TOC evolution in the Iberian Peninsula was studied in depth by Román et al (2014d) in the dimming and brightening periods, with usually negative but not statistically significant trends being reported in both periods, and a statistically significant trend of −0.7 % dc −1 (percent per decade units) in the annual TOC between 1950 and 2011. Antón and Mateos (2013) showed that these TOC changes have no significant influence on SW radiation (e.g.…”
Section: R Román Et Al: Erythemal Ultraviolet Irradiation Trends Inmentioning
confidence: 99%
“…Recently, Román et al (2014d) obtained the TOC trends from 1950 to 2011 on the Iberian Peninsula, and Román et al (2014a) the SW and temperature trends for the same period and region, but not the UVER trends due to the lack of UVER data. As a first step, Román et al (2014b) simulated the UVER irradiance under cloudless conditions on the Iberian Peninsula with a radiative transfer model, using as inputs monthly climatological values of aerosols, water vapour, etc.…”
Section: R Román Et Al: Erythemal Ultraviolet Irradiation Trends Inmentioning
confidence: 99%
See 3 more Smart Citations